The Determinants of Financial Inclusion in Tanjungpinang City - Octojaya Abriyoso; Dwi Septi Haryani; Raja Hardiansyah (Research Synergy Foundation, 2022)
As we know in many developing countries as like Indonesia, the financial sector is ncluding banking sector, then post office and also non-banking financial intermediaries. Though, a huge amounts of payments of finance through diversified manner occurred by the network of banking institutions in the extension event of banking services to rural areas. This research was on purpose to help finding out the way the factors creating Financial Inclusion spesifically in archipelagic areas that is known as the most its people own certain characteristics of demographic. This research applied method of multinomial logistic regression process of analysis. The sample is the 200 people of Tanjungpinang city aged 18 years and over who are already working and have a bank account along with M-Banking. It was concluded that groups with older age, male, higher education, longer distance towards financial institution, easily arrange the document regarding the financial products, have trust in the institution, have higher income, and have a proper internet access are have a higher probability to embrace the inclusion than the other group who doesn’t.